Economic Performance of Selected Dairy Breeds in Ayodhya Mandal, Uttar Pradesh - Dwivedi, Shripati; Singh, Ajmer; Chandel, B S; Kumar Patel, Deepak; Dube, Alok (Indian Journal of Extension Education, 2024)
The study estimated the milk production in the Ayodhya mandal of Uttar Pradesh for selected dairy breeds, Sahiwal, Murrah, and Crossbred (with jersey) during the years 2020-2021. Using a pre-tested structured schedule, primary data was collected on 108 dairy animals of the selected dairy breeds and their respective lactation groups. This study used the snowball sampling technique to select animals from different lactation groups and the budgetary technique to calculate the costs and returns. There was a significant increase in the cost of milk production, which was measured by the cost of milk per liter 1.18 times, 1.15 times, and 1.10 times, respectively, in the Sahiwal, Crossbred cow, and Murrah groups as compared to the first to third lactation groups, for milk production during the 7th lactation and above. For the same lactation group of Sahiwal, Crossbred cow, and Murrah, the net return per liter declined by 36 per cent, 17 per cent, and 21 per cent, respectively, for the same group of Sahiwal, Crossbred cow, and Murrah cows.
Keywords: Breeds; Cost; Dairy; Lactations; Milk production; Productive life; Returns